Dysbiosis and depressive disorders. Survey review - Janik, Inga; Maciejewska, Martyna; Korabiusz, Katarzyna; Wawryków, Agata; Wilczyńska, Agnieszka; Stecko, Monika; Fabian-Danielewska, Anna (Journal of Education, Health and Sport, 2019)
A significant increase in the incidence of depression, change of lifestyle and nutrition, forces researchers to seek understanding of the various mechanisms of the formation of such a disorder. Numerous studies draw attention to dysbiosis - a disorder of the composition and function of the intestinal microflora. In current studies, strong correlations can be observed between microbiota disorders and the occurrence of autoimmune and inflammatory diseases.